Normative Problems Guaranteeing the Rights of Labor Fishermen in the Job Creation Law - Dhaniar Eka Budiastanti; Galih Puji Mulyono; Dewi Ayu Rahayu; Bintang Ulya Kharisma; Selvi Andriani (Faculty of Law, University of Merdeka Malang, 2023)
The substance of the Job Creation Act in Indonesia covers all areas of law. This paper only examines the elements of labor law, especially those related to guaranteeing legal rights for labor fishermen in Indonesia. This research is based on legal problems where the legal relationship between fishermen and labor fishermen is from the point of view of the Job Creation Act, so the ultimate goal of this research is to explain the guarantee of labor fishermen's rights. The approach used in this research is normative juridical by collecting data collection tools in the form of normative literacy studies related to these problems. The working relationship between owner and labor fishermen is legal because all these jobs contain elements of an employment relationship. The type of work agreement made between owner fishermen and labor fishermen is a verbal agreement. The legal consequence is that the rights of labor fishermen after the termination of employment are not granted due to the low position of labor fishermen. All workers, especially labor fishermen, should accept the rights in the Job Creation Law.How to cite item: Budiastanti, Dhaniar Eka, Galih Puji Mulyono, Dewi Ayu Rahayu, Bintang Ulya Kharisma, and Selvi Andriani. â€œNormative Problems Guaranteeing the Rights of Labor Fishermen in the Job Creation Law.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023):Â 167-176. DOI: doi.org/10.26905/idjch.v14i2.10864.